(untitled) (LACCEI, 2024)
The main objective of this study was to determine how credit and collection management affects the liquidity of the company AFA GROUP of Trujillo in the year 2022. This is a mixed-applied, non-experimental, longitudinal and descriptive-explanatory study, which includes as study population the company AFA GROUP and evaluates three periods: 2019, 2020 and 2021. Interviews and documentary analysis were used for data collection. The results indicate that inefficient credit and collection management has a negative impact on the liquidity of the company AFA GROUP, reducing its liquidity ratios by 77% in 2021. In that year, the company had particular difficulties in meeting its short-term debts, with an acid test ratio of 0.39 and a cash ratio of 0.03. In conclusion, it was determined that poor accounts receivable management can generate liquidity problems and make it difficult to meet obligations to third parties.